Institutionalisation beyond the Nation State Transatlantic Relations: Data, Privacy and Trade Law (Studies in European Economic Law and Regulation, 2018)
This volume collects papers that explore institutionalisation in contemporary transatlantic relations. Policymakers, lawyers, and political scientists reflect on contemporary understandings of the process as an integration of regimes and orders from an EU perspective. The papers assess whether contemporary transatlantic relations call for a different approach to global governance with a heightened emphasis on institutionalisation. The book explores a diverse range of case studies of interest to a broad readership. In particular, it focuses upon two cutting-edge issues: transatlantic data privacy rules that are emerging after the post-Edward Snowdon / NSA / PRISM revelations; and trade aspects, especially the Transatlantic Trade and Investment Partnership (TTIP) Agreement. The contributors consider these case studies from a variety of perspectives, honing in on the dynamism, method, and high politics of transatlantic relations as they have recently evolved. They critically explore the commonly held assumption that transatlantic relations have historically been considered quasi-institutionalised at best or, at worst, lacking in terms of laws and institutions. Is institutionalisation a useful meeting point for all disciplines? Does it explain regional integration meaningfully across subjects? Can institutionalisation serve to promote accountability and good governance? Contributors across disciplines and subjects address these increasingly challenging and salient questions. .